Control of massive cardiac haemorrhage by balloon catheter. Issue 3 (May 1973) - Dube, P.
Abstract : The use of a balloon catheter to achieve the control of haemorrhage from the chambers of the heart has not been described previously. A case is reported in which this method was used in an emergency situation. It has been tested successfully, as a planned procedure, during four closed mitral valvotomy operations. Balloon catheters have been used in vascular surgery for some time. Taylor and Williams (1962) used a Foley's catheter to prevent haemorrhage from an arteriovenous fistula at the time of its repair. Fogarty et al. (1963) described the use of Fogarty's catheter during extraction of arterial emboli and thrombi. Control of hepatic venous bleeding by placing a balloon catheter in the inferior vena cava in seven dogs was described by Doty and Berman (1970), and Foster, Morgan, and Threlkel (1971) used balloon catheters to achieve proximal control of the abdominal aorta. Thomas (1971) described the use of Fogarty catheters and Bakes common bile duct dilators to control bleeding during operation in complicated peripheral vascular lesions. Arbulu and Thomas (1972) reported a case of a gunshot wound in which haemorrhage from the inferior vena cava close to the heart was controlled by using a Foley's catheter.